Review of The life of José María Sobral: scientist, diarist, and pioneer in Antarctica, by Mary R. Tahan (2018). Cham, Switzerland: Springer International Publishing. 336 pp. ISBN 978-3-319-67267-0 - Millar, Pat (Polar Research, 2019)
Keywords: Antarktis; Otto Nordenskjöld; bokanmeldelser; dagbøker; ekspedisjoner; geodesi; magnetisme; meteorologi; oppdagelsesreiser

Kaptein Melsom. Et spennende liv som hvalfanger og skipsreder - Dyrhaug, Tore (Njotarøy : årsskrift, 2015)
1912 fikk Nøtterøy en ny innbygger. Hvalfangeren H. G. Melsom var vendt hjem fra et hvalfangerliv i det fjerne Østen og kjøpte hus på Ørsnes. Her startet han opp en ny fase i livet, som skipsreder. Høydepunktet i hans karriere var trolig da hvalskuta «Lancing» dro om bord den første hvalen fra en opphalingsslipp i hekken på båten. Med dette var den virkelige pelagiske hvalfangsten i gang. Historien om «Lancing» som det første hvalkokeriet som kunne dra en hel hval om bord, er vel kjent og beskrevet. Dette var starten på den pelagiske hvalfangsten som brakte hvalfangsten inn i en ny fase. Men historien om hvalfangeren og rederen fra Nøtterøy, som var en av dem som sto bak, har ikke vært særlig kjent. Med god hjelp fra barnebarnet Henrik Melsom Henriksen, har Tore Dyrhaug skrevet ned denne historien.
Publisher: Nøtterøy historielag
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Review of Race for the South Pole: the expedition diaries of Scott and Amundsen, by Roland Huntford - Jølle, Harald Dag (Polar Research, 2012)
Roland Huntford is the grand old man among polar historians. After his classic Scott and Amundsen in 1979 (later editions were retitled, The last place on Earth), he wrote a series of books on Norwegian and British polar heroes as well as a thorough study of the history of skiing (2006). Huntford challenged the British admiration of Robert Falcon Scott’s scientific programme and great courage*and insisted that Roald Amundsen’s expedition was far better prepared and carried out. Huntford’s scathing criticism of Scott’s fatal choices and lack of competence dared to assault this cherished British polar icon in a manner that would be unthinkable for Norwegian authors.
Keywords: Antarktis; Roald Amundsen; Robert Falcon Scott; Sydpolen; Sydpolsekspedisjonen; Sørpolen; bokanmeldelser; dagbøker; kappløpet; polarhistorie; polarområdene

The first Antarctic whaling season of Admiralen (1905–1906): the diary of Alexander Lange - Adie, Susan; Basberg, Bjørn L; Lange, Alexander (Polar Record, 2009)
The first factory ship of the so-called modern era of Antarctic whaling was Admiralen, arriving together with two smaller catcher boats in the South Shetland Islands in January 1906, after a period of whaling in the Falkland Islands. The expedition leader was Alexander Lange, a Norwegian whaler with a long experience from whaling in northern Norway and Spitsbergen. He kept a diary for a considerable period and this covered several whaling voyages. The one dealing with the pioneer Antarctic season of 1905–1906 has been translated from Norwegian into English and is presented here with an introduction that places the expedition into its wider context.
Publisher: Cambridge University Press
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Review of Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition, by M.L. Paine - Baughman, Timothy H (Polar Research, 2008)
If the reader is looking for another rehashing of one of the adventures of the “Heroic Era” of Antarctic exploration, or another reshaping of the same old material about the three or four explorers from that period who get all the attention, M.L. Paine’s Footsteps on the ice: the Antarctic diaries of Stuart D. Paine, Second Byrd Expedition is not the book for you. But if you are a serious Antarctic buff who wants to learn something new, and really get inside one of the early expeditions of the 20th century, Paine’s volume will be a compelling read.
Keywords: Antarktis; Richard Evelyn Byrd; Sydpolflyvningen; bokanmeldelser; dagbøker; ekspedisjoner; fly; luftfart; oppdagelsesreiser; polarflyving; turisme

Roald Amundsen : tidenes polfarer - Barr, Susan; Amundsen, Roald; Ekeberg, Jan Ove (Stenersen forl., 2005)
Keywords: Antarktis; Belgica ekspedisjon; Roald Amundsen; Sydpolsekspedisjonen; biografier; dagbøker; oppdagelsesreiser

Dagbok fra en Sydhavstur 1906 - Sørlle, Petter; Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2005)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Sørishavet; dagbøker; hvalfangere; hvalfangstindustri; hvalindustri; hvalkokeri; polareksspedisjoner

Blant pelssel og pingvinar. Ei julereise til Sør-Georgia og Antarktis - Kolltveit, Bård (Norsk sjøfartsmuseum. Årbok, 2003)
Publisher: Norsk sjøfartsmuseum Place: Oslo
Keywords: Antarktis; cruiseturisme; dagbøker; polareksspedisjoner; reisebeskrivelser; reiseskildringer

Skipsdagboken fra hvalkokeriet "Pythia" : beriberi utbruddet i 1928 - Børresen, Dag Ingemar (Sandar historielag, 2002)
Keywords: Norge; Sørishavet; dagbøker; hvalfangst; hvalkokerier